APRM Country Review Report Mozambique - República de Moçambique (República de Moçambique, 2009)
The major cross-cutting issues which featured prominently in all the thematic areas are highlighted below. A comprehensive approach is needed to address these issues as they have wider ramification for the various dimensions of governance in Mozambique. The following are the major thirteen crosscutting issues emerging from this report: Poverty and Inequality; Party/government/business dichotomy; HIV/AIDs; Land Ownership; High levels of illiteracy; High aid dependency; Information flow and paucity of data; Inclusivity; Crime, safety and Security; Domestic violence; Capacity constraints and implementation challenge; Elections; and, Corruption. CONCLUSION: The remarkable recovery that Mozambique has made since the end of the civil war in 1992 should make the people proud of their accomplishments. Over the last two decades, Mozambicans has made considerable progress in rebuilding its political, economic and social institutions, with noticeable progress. There is no doubt that Mozambicans can build on the successes highlighted in this report, while addressing the challenges in a vigorous manner, in order for the country to rapidly move forward. With its abundant natural resources, Mozambicans can exploit these resources for the benefit of the majority of its people. But this will be difficult to achieve without pragmatic and innovative solutions to the challenges arising from both the thematic and cross-cutting issues identified by this report.
Keywords: *non-public; G - Mozambique / Moçambique; L - english / inglês; conflict - civil war / conflito - guerra civil; governance / governação; health / saúde; natural resources / recursos naturais; poverty / pobreza

Social Protection in Mozambique: A new imperative? - Waterhouse, Dr Rachel; Lauriciano, Gil (IESE Conference ‘Poverty Dynamics and Patterns of Accumulation in Mozambique, 2009)
Even before the impact of a global economic crisis kicks in, there is renewed thinking in Mozambique about a wider role for the state in social protection. Proponents are still struggling to convince others of the economic and social value of a broader investment in social protection. This is against the backdrop of institutional resistance borne of Mozambique’s political and economic history. The government attitude to social protection has been influenced by colonial experience of an extractive rather than protective state and the legacy of post-Independence events and processes. After Independence in 1975, initial social service expansion was heavily undermined by war-time destruction and economic collapse in the 1980s. Post war, the Government’s top priorities were to re-establish security and rebuild infrastructure. However, political and economic liberalisation in the 1990s saw tight caps on state spending. Poverty was so widespread and deep that there seemed to be little scope for special consideration of the ‘poorest of the poor’... except for ad hoc initiatives, such as the food subsidy programme for the poor and unable to work. In the last 15 years, Mozambique has experienced impressive economic growth and poverty reduction. Nonetheless Mozambique continues to rank amongst the world’s poorest countries. Government is becoming more aware of chronic poverty and that large population groups are currently unable to escape the poverty trap. This raises debate about what can be done ... and promotes renewed thinking on social protection. There are still many obstacles to a coherent and comprehensive approach to social protection. These include: analytical limitations around the causes, consequences and extent of vulnerability as well as the potential social and economic benefits of social protection; institutional barriers; budgetary limitations; and perceived political risk. However, there is also a growing acceptance of the relevance and importance of social protection to reduce vulnerability, build resilience and contribute to poverty reduction. These issues need to be addressed at policy and practical level, if Mozambique is to effectively address the growing challenge of chronic poverty.
Keywords: *tagged; Ethnographic Studies; G - Mozambique / Moçambique; L - english / inglês; poverty / pobreza; social protection / proteção social

Gender and Poverty in Northern Mozambique - Tvedten, Inge; Paulo, Margarida; Tuominen, Minna (Chr. Michelsen Institute, 2009)
The main objective of this report is to capture the local configurations of gender relations in Nampula, by focussing on one rural and one urban area in the province. The former is the coastal and rural district of Mossuril, which is considered one of the most deprived districts in the province, both in terms of material poverty and human development (MAE 2005). The urban areas are Muatala and Namutequeliua, which are two of the most populous bairros in the city of Nampula and largely inhabited by migrants from the coast and hence share historical and sociocultural roots with Mossuril.
Keywords: *snowball; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Mossuril; GP - Nampula; Health PEA; L - english / inglês; education / educação; employment / emprego; gender / género; health / saúde; poverty / pobreza

Monitoring and Evaluating Mozambique’s Poverty Reduction Strategy PARPA 2006-2008. A Synopsis of Three Qualitative Studies on Rural and Urban Poverty. - Tvedten, Inge; Rosário, Carmeliza; Paulo, Margarida (Chr. Michelsen Institute, 2009)
The purpose of this synopsis is to facilitate discussions between the government, civil society organisations, donors and other stakeholders in Mozambique’s efforts to reduce poverty and, more specifically, to contribute to the Impact Assessment Report (Relatótio de Avaliação de Impacto, RAI) which is to be carried out in 2009. We will focus on our main findings and preliminary conclusions, and will to the extent possible avoid repeating data found in the original reports to ease accessibility. The discussions related the synopsis will also be used to further identify the most relevant topics and approaches for the final three studies, in order to secure their maximum utility for the government’s monitoring and evaluation programme. The synopsis will be divided into six parts following this Introduction. In Chapter 2 we briefly account for the analytical framework and methodological approaches of the studies. In Chapter 3 we present what we have identified as aspects of Mozambique’s political economy with particular impacts on the situation in local communities. In Chapter 4 we analyse the main features of the political context at the level of districts through which poverty reduction is implemented. In Chapter 5 we present the main findings from the adapted surveys we have carried out, with a focus on the similarities and differences between the three areas of study. In Chapter 6 we assess the outcome of our qualitative and participatory approaches to our analyses. And finally, in Chapter 7, we present preliminary conclusions and recommendations from the first three studies and outline the approach of the three follow-up studies.
Keywords: G - Mozambique / Moçambique; L - english / inglês; M - evaluation / avaliação; poverty / pobreza; urbanization / urbanização